Media framing and trust: A randomized survey experiment on attitudes towards the unvaccinated during the COVID-19 pandemic - Koivula, Aki; Marttila, Eetu; Koiranen, Ilkka (Elsevier Ltd, 2025)
This research examines the influence of news media and trust in institutions on how vaccinated individuals in Finland perceived the unvaccinated during the COVID-19 pandemic. The study employed a randomized survey experiment involving 455 participants and incorporated episodic and thematic news framings on vaccine side effects alongside a non-treatment control group. Episodic framing, which presented personal stories, was found to significantly reduce the inclination to impose additional restrictions on the unvaccinated and lessen the perception of them as an outgroup. The converse effect was shown in thematic framing, which focused on statistics and expert opinions. The study also underscored the pivotal role of trust in institutions: lower trust increases the influence of episodic framing, while strong political trust can mitigate the effects of news framing. This investigation provides vital insights into the interplay between media framing and trust levels in shaping public attitudes towards health risks and non-adherence during a health emergency.